Analisis Dampak Pandemi Covid-19 Mengenai TPT Provinsi/Kota Indonesia Tahun 2020 - Azizah, Wafidz; Mahendarta, Denara Syafira; Desmawan, Deris (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Abstract.nalysis of the effect of covid-19 pandemic on TPT in Indonesia. The research aims to determine the variables that dominate Indonesian TPT in 2020. The research used secondary variables in government agencies with a total of 1 year related to cross sectional data, namely the classic assumption test, normality test, multicollinearity test, heteroskedaticity test and autocorrelation test. The research system used in this study is spss 23 software because it is necessary to understand the influence of free components on TPT in Indonesia. The Output of this research, it was found that independent variables have a partially relevant impact. Positive variables of Covid-19, recovering from Covid-19, deaths from Covid-19 and unemployment rate were partially significant.